Abundant optical structures of the (2+1)-D stochastic chiral nonlinear Schrodinger equation - Arshed, Saima; Raza, Nauman; İnç, Mustafa; Khan, Kashif Ali (Springer, 2023)
The current study deals with the exact results of the (2+1)-dimensional stochastic chiral nonlinear Schrodinger equation (SCNLSE). For this, a complex transformation is applied instantly to achieve the imaginary and parts, and then the two efficient integrating techniques such as the G ' /G,1/G expansion method, tan( phi(epsilon) / 2 )-expansion approach is impleG mented to obtain new periodic solutions, hyperbolic solutions, and rational solutions. Most important, the influence of the multiplicative noise on the results of SCNLSE will be disseminated. In addition, 3D plots of a few of the solutions acquired are shown in this work to corroborate our findings.
Keywords: (G' /G,1/G)- expansion; tan( f(e) / 2 )- expansion approach; Solitons